2020
DOI: 10.1186/s12877-020-01523-w
|View full text |Cite
|
Sign up to set email alerts
|

Plasma 25-hydroxyvitamin D level and the risk of frailty among Chinese community-based oldest-old: evidence from the CLHLS study

Abstract: Background Vitamin D deficiency has been linked to the risk of frailty. However, there are limited methods for evaluations of the potential association of vitamin D with frailty in a longevous (80+) population. The aim of this study was to examine the association between plasma 25-hydroxyvitamin D [25(OH)D] levels and the risk of frailty among the Chinese community based oldest-old. Methods Secondary analysis of data compiled in the 2011 wave of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Additionally, multidimensional logistic regression models indicated a significant inverse relationship between the level of 25(OH)D and the risk of frailty and geriatric syndrome (74).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Additionally, multidimensional logistic regression models indicated a significant inverse relationship between the level of 25(OH)D and the risk of frailty and geriatric syndrome (74).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Levels of total cholesterol are inversely associated with plasma 25-hydroxyvitamin D levels, 40 which are an important Open access marker for frailty among Chinese community-dwelling older adults. 41 Levels of total cholesterol are also inversely associated with lean body mass, 42 which is important to determine risks of falls in older Asian adults. 43 However, plasma 25-hydroxyvitamin D and lean body mass were not measured in the CHARLS, so we were not able to examine whether these two biomarkers may explain the association between levels of total cholesterol and fall events in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, if it is difficult to completely reverse the phenomenon, thereby necessitating the development of a convenient and rapid early warning tool. Xiao et al [ 15 ] pointed out that vitamin D deficiency or insufficiency is positively correlated with cognitive frailty, while Chye et al [ 16 ] showed that lack of vitamins C and E could easily lead to cognitive frailty in the elderly. However, these risk factors need to be detected by the instrument.…”
Section: Introductionmentioning
confidence: 99%